2022
DOI: 10.3390/ijms23031646
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Flexibility and Local Frustration in the Functional States of the SARS-CoV-2 Spike B.1.1.7 and B.1.351 Variants: Mutation-Induced Allosteric Modulation Mechanism of Functional Dynamics and Protein Stability

Abstract: Structural and functional studies of the SARS-CoV-2 spike proteins have recently determined distinct functional states of the B.1.1.7 and B.1.351 spike variants, providing a molecular framework for understanding the mechanisms that link the effect of mutations with the enhanced virus infectivity and transmissibility. A detailed dynamic and energetic analysis of these variants was undertaken in the present work to quantify the effects of different mutations on functional conformational changes and stability of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…Such movements might favor ACE2 binding [ 31 ] by scanning the surrounding space for a possible alignment with the receptor, while indirectly exposing cryptic epitopes. [ 16 ] These findings, in context with the cryo‐EM results, [ 18,32 ] highlighted the importance of S2 flexibility, which plays a crucial role in conformational changes, [ 33 ] alignment, and membrane fusion process. [ 7,16 ] However, the limitations of the timescale in MD simulations restrict the exploration of long‐lasting contacts between the protein and the receptor, thus limiting our ability to characterize the interaction network that contributes to the binding process.…”
Section: Molecular Dynamics Simulations Uncover the S Protein Flexibi...mentioning
confidence: 81%
“…Such movements might favor ACE2 binding [ 31 ] by scanning the surrounding space for a possible alignment with the receptor, while indirectly exposing cryptic epitopes. [ 16 ] These findings, in context with the cryo‐EM results, [ 18,32 ] highlighted the importance of S2 flexibility, which plays a crucial role in conformational changes, [ 33 ] alignment, and membrane fusion process. [ 7,16 ] However, the limitations of the timescale in MD simulations restrict the exploration of long‐lasting contacts between the protein and the receptor, thus limiting our ability to characterize the interaction network that contributes to the binding process.…”
Section: Molecular Dynamics Simulations Uncover the S Protein Flexibi...mentioning
confidence: 81%
“…For this reason, we excluded the terminal four N-terminal amino acids for the successive docking studies. Computational studies have suggested high flexibility of the SP stalk due to the presence of two unstructured knees 63 . Our simulations displayed similar behavior, where the bending of the stalk was aided by the opening of transitory pockets within the flexible loops, which temporarily moved away more than 20 Å from each other ( Figure 3B ) with an angle of about 133° between the alfa carbons of P1143-V1164-I1172 ( Figure S1) .…”
Section: Resultsmentioning
confidence: 99%
“…Stability analysis of chemical bond interactions in ligand-protein interaction hot spots is performed through molecular dynamic simulation on the CABS-flex 2.0 server (http://biocomp.chem.uw.edu.pl/CABSflex2) [29]. This server identifies the stability of ligand-protein molecular complexes by calculating structural flexibility through large-scale conformational simulations.…”
Section: Objects and Methodsmentioning
confidence: 99%
“…This server identifies the stability of ligand-protein molecular complexes by calculating structural flexibility through large-scale conformational simulations. The output score of the simulation results is the root-mean-square fluctuation (RMSF) for the determination of molecular complex stability [29,30].…”
Section: Objects and Methodsmentioning
confidence: 99%